Between the Flowers : A Novel - Arnow, Harriette Louisa Simpson, 1908-1986 (Book collections on Project MUSE., 1999)
A 1930s novel set in Appalachia on the drama of a woman with imagination, married off to an ordinary farmer. A look at what life was like for some women before feminism came along. By the author of The Dollmaker.